Visualisasi Berbasis Web Indeks Aksesibilitas Fasilitas Kesehatan di Kota Bogor - Rina Trisminingsih; Citra Hasana Sagala (P4W LPPM IPB, 2017)
Bogor City has health facilities about 19 hospitals, 24 puskesmas, and 94 clinics. Accessing health facilities need some consideration such as distance or accessibility to the health facilities. The objective of the research is to determine and present accessibility index to the health facilities. Accessibility/Remoteness Index of Australia (ARIA) method is chosen to calculate and classify the accessibility index of health facilities in Bogor City. There are several steps to do such as making basic map, calculating and classifiying accessibility index, then developing visualization module. Web-based visualisation modul is developed by OpenGeo suite technology. Accessibility index calculation is held in an area (grid and kelurahan) to the health facilities (hospitals, puskesmas, clinics). The results obtained 2.27% grid and 8.46 % villages in Bogor City has low level access to all health facilities. From the visualization showed that Mulyaharja village is an area which have the lowest accessibility index in Bogor City.